Can Short-Term Ocular Dominance Plasticity Provide a General Index to Visual Plasticity to Personalize Treatment in Amblyopia? - Tao, Chunwen; He, Zhifen; Chen, Yiya; Zhou, Jiawei; Hess, Robert F. (Frontiers in Neuroscience, 2020)
Purpose Recently, Lunghi et al. (2016) showed that amblyopic eye’s visual acuity per se after 2 months of occlusion therapy could be predicted by a homeostatic plasticity, that is, the temporary shift of perceptual eye dominance observed after a 2-h monocular deprivation, in children with anisometropic amblyopia. In this study, we assess whether the visual acuity improvement of the amblyopic eye measured after 2 months of occlusion therapy could be predicted by this plasticity. Methods Seven children (6.86 ± 1.46 years old; SD) with anisometropic amblyopia participated in this study. All patients were newly diagnosed and had no treatment history before participating in our study. They finished 2 months of refractive adaptation and then received a 4-h daily fellow eye patching therapy with an opaque patch for a 2-month period. Best-corrected visual acuity of the amblyopic eye was measured before and after the patching therapy. The homeostatic plasticity was assessed by measuring the temporary shift of perceptual eye dominance from 2-h occlusion of the amblyopic eye before treatment. A binocular phase combination paradigm was used for this study. Results We found that there was no significant correlation between the temporary shift of perceptual eye dominance observed after 2-h occlusion of the amblyopic eye and the improvement in visual acuity in the amblyopic eye from 2 months of classical patching therapy. This result, although in disagreements with the conclusions of Lunghi et al. involving the short-term patching of the amblyopic eye, is in fact consistent with a reanalysis of Lunghi and colleagues’ data. Conclusion The short-term changes in perceptual eye dominance as a result of short-term monocular deprivation do not provide an index of cortical plasticity in the general sense such that they are able to predict acuity outcomes from longer-term classical patching.